Kepemimpinan Pendidikan Berbasis Pendidikan Karakter Dalam Pembelajaran Praktikum Fisika Di Sekolah - Ikram Ramadhan (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
Character education is the main capital that must be instilled in children from an early age, because the concept of character education is indispensable in every dimension of life. Character education in the field of education is the main focus to achieve educational goals. With character education, children will have the ability to behave positively both in the school environment and in the community. This study aims to identify the values of student character behavior that appear according to Presidential Regulation No. 87 of 2017 concerning strengthening character education article 3. This type of research is phenomenological research with data collection techniques using the observation method. The data analysis technique used in this research is to use the method of data reduction, interpretation and drawing conclusions. The results showed 1) of the 18 character behaviors according to Presidential Regulation No. 7 of 2017, there were 15 character behaviors that emerged from students in physics practicum, 2) there were 3 character behaviors that did not appear, namely independent behavior, love for the homeland and national spirit, 3) The character behavior of students in one school illustrates that the leadership of character education-based education in that school is going well.